2009
DOI: 10.1245/s10434-009-0809-6
|View full text |Cite
|
Sign up to set email alerts
|

Local and Distant Immunity Induced by Intralesional Vaccination with an Oncolytic Herpes Virus Encoding GM-CSF in Patients with Stage IIIc and IV Melanoma

Abstract: Melanoma patients present with elevated levels of Tregs, Ts, and MDSC within established tumors. Direct injection of Oncovex(GM-CSF) induces local and systemic antigen-specific T cell responses and decreases Treg, Ts, and MDSC in patients exhibiting therapeutic responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
358
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 469 publications
(366 citation statements)
references
References 38 publications
7
358
0
1
Order By: Relevance
“…A number of preclinical studies have shown that oncolytic herpes viruses induce cytotoxic T lymphocyte-mediated antitumor immunity, which can inhibit tumor regrowth upon rechallenge. [33][34][35][36] Consistent with this, efforts have been made to arm oncolytic herpes viruses with cytokines such as interleukin-12 37 and granulocyte-macrophage colony-stimulating factor 10,38 in order to intensify antitumor immunity. From this perspective, it might be said that the potency of a virus relies on its capacity to induce antitumor immunity.…”
Section: Introductionmentioning
confidence: 91%
“…A number of preclinical studies have shown that oncolytic herpes viruses induce cytotoxic T lymphocyte-mediated antitumor immunity, which can inhibit tumor regrowth upon rechallenge. [33][34][35][36] Consistent with this, efforts have been made to arm oncolytic herpes viruses with cytokines such as interleukin-12 37 and granulocyte-macrophage colony-stimulating factor 10,38 in order to intensify antitumor immunity. From this perspective, it might be said that the potency of a virus relies on its capacity to induce antitumor immunity.…”
Section: Introductionmentioning
confidence: 91%
“…The most promising immunotherapy strategies for melanoma so far have included the combination of the adjuvant GM-CSF with ipilimumab (32), which is an anti-CTLA-4 antibody, and the recombinant viral vector-based vaccine OncoVex GM-CSF , now known as T-VEC (talimogene laherparepvec; refs. [33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been demonstrated that the oncolytic efficacy of an attenuated HSV vector may be increased by the virally induced antitumor immunity, 32 either locally by the recruitment of immune effector cells, which may increase oncolytic activity and improve tumor clearance, or at distant sites by cross-priming the immune response to the tumor. 33 With this respect, in some instances HSVs have been armed in order to achieve a better immune-mediated tumor killing. 34,35 Syngeneic models for gliomas have been developed in rats and mice.…”
Section: Discussionmentioning
confidence: 99%